2020
DOI: 10.4028/www.scientific.net/msf.978.183
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose Based Composites: Preparation and Characterization

Abstract: Bacterial Cellulose (BC) is a biologically derived material having properties that present it as a biomaterial, with potential application in various fields. BC based composites capitalize its properties and enhance its applications. Bacterial cellulose composites were prepared with poly (methyl methacrylate) and polyvinyl alcohol and characterized for optical transmittance, structural properties and tensile test. The transmittance of composites was found to be decreased for higher BC content in composites. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several studies have contributed valuable insights into various aspects of this research area, encompassing the utilization of bacterial cellulose and its composites, incorporation of bioactive compounds, and enhancement of barrier properties for food preservation. Choudhary et al explored the preparation and characterization of bacterial cellulose-based composites [1]. Revin et al provided a comprehensive review of bacterial cellulose-based polymer nanocomposites [2], while Mbituyimana et al discussed research progress and existing products in bacterial cellulose-based composites for biomedical and cosmetic applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have contributed valuable insights into various aspects of this research area, encompassing the utilization of bacterial cellulose and its composites, incorporation of bioactive compounds, and enhancement of barrier properties for food preservation. Choudhary et al explored the preparation and characterization of bacterial cellulose-based composites [1]. Revin et al provided a comprehensive review of bacterial cellulose-based polymer nanocomposites [2], while Mbituyimana et al discussed research progress and existing products in bacterial cellulose-based composites for biomedical and cosmetic applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Dahman study showed that polyurethane reinforced with bio-cellulose nano bers with improvements in biological compatibility and mechanical properties has a strong potential for bone transplants and other tissue engineering applications [18]. Besides, some biodegradable nanocomposite materials have been studied based on polymers such as polyvinyl alcohol [19], polylactic acid [20], polymethyl methacrylate [21], starch [22], and epoxy [23][24][25]. In addition to the polymer, various nanoparticles (titanium dioxide) [26,27] and plant extracts have also been combined with BC to enhance its properties and impart new functions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…e structure of the yarn is preserved, and the yarn has many special properties, including bacterial cellulose fibers. Bacterial cellulose (BC) fibers with purity, purity, and high content have been noticed by many scientists [14][15][16][17][18]. Epoxy is widely used with good mechanical properties and high compatibility with reinforcing materials of natural origin selected for the manufacture of synthetic materials with natural fiber reinforcement.…”
Section: Introductionmentioning
confidence: 99%